Hypoglycemia in carbon monoxide poisoning: A case report - Arora, Akant; Desai, Krunal; Jain, Sandeep; Mehta, Manish (Indian Journal of Case Reports, 2019)
Carbon monoxide poisoning is a common presentation in the Emergency Department. The clinical presentation runs a spectrum, ranging from headache and dizziness to coma and death, with a mortality rate ranging from 1 to 3 %. Administration of normobaric 100% oxygen is the therapy of choice for most cases, while hyperbaric oxygen therapy is reserved for severe poisoning. Hyperglycemia is commonly seen with this poisoning but the association of hypoglycemia is not well described in human studies. Here, we present the case of hypoglycemia in carbon monoxide poisoning with good clinical outcome in a 22-year-old male.